Algometer Assessment of Pressure Pain Threshold After Onabotulinumtoxin-A and Physical Therapy Treatments in Patients With Chronic Migraine: An Observational Study - Deodato, Manuela; Granato, Antonio; Ceschin, Marta; Galmonte, Alessandra; Manganotti, Paolo (Frontiers in Pain Research, 2022)
The purpose of this study was to evaluate pain hypersensitivity in chronic migraine patients 3 months after undergoing onabotulinumtoxin-A therapy, physical therapy (PT), or the combination of the two. Pressure pain threshold (PPT) was assessed in accordance with Andersen's guidelines, focusing on five muscles in the trigeminocervical area (namely, trapezius, levator scapulae, temporalis, sub-occipitalis, and scalenus medius) and one muscle outside of the area, (i.e., tensor fasciae latae). Moreover, three headache parameters, namely, attack frequency, duration, and pain intensity, were recorded in an ad hoc diary kept by the patients. A total of 30 patients were included in three treatment groups: 1. onabotulinumtoxin-A therapy, 2. PT, and 3. a combination of onabotulinumtoxin-A and PT. The results show that, at the final assessment, the PPT was significantly reduced in the combined treatment group compared to the two single-therapy groups. As regards headache parameters, frequency and duration of the attacks were decreased significantly in all three treatment groups, whereas in pain intensity, the reduction was statistically significant in the combined treatment group and the onabotulinumtoxin-A therapy. Results suggest that a better pain modulation in patients with chronic migraine can be achieved with a combined treatment of onabotulinumtoxin-A and physical therapy. Indeed, the combination of both pharmacological and non-pharmacological treatments results in the reduction of both headache-related parameters and widespread pressure hyperalgesia.